2015
DOI: 10.1002/bio.2905
|View full text |Cite
|
Sign up to set email alerts
|

Utility of eosin Y as a complexing reagent for the determination of citalopram hydrobromide in commercial dosage forms by fluorescence spectrophotometry

Abstract: An accurate, selective and sensitive spectrofluorimetric method was developed for the determination of citalopram hydrobromide in commercial dosage forms. The method was based on the formation of a fluorescent ion-pair complex between citalopram hydrobromide and eosin Y in the presence of a disodium hydrogen phosphate/citric acid buffer solution of pH 3.4 that was extractable in dichloromethane. The extracted complex showed fluorescence intensity at λem = 554 nm after excitation at 259 nm. The calibration curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In the literature, it was reported that chlorpheniramine [14], doxepin HCl [15], citalopram HBr [16] and imipramine [17] of the diphenhydramine and -C=O of eosin Y. The reaction sequence is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it was reported that chlorpheniramine [14], doxepin HCl [15], citalopram HBr [16] and imipramine [17] of the diphenhydramine and -C=O of eosin Y. The reaction sequence is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Extractive spectrofluorimetric methods were reported for some drugs based on either binary or ternary complex formation with eosin Y. Binary complex formation was applied for the determination of citalopram hydrobromide (Azmi et al 2015) and doxepin hydrochloride (Rahman, Siddiqui & Azmi, 2009) in commercial dosage forms. The method was based on the formation of an ion-pair complex between the drug and eosin Y in the presence of acetate buffer (at pH 3.4 for citalopram and pH 4.52 for doxepin).…”
Section: Extractive Spectrofluorimetric Methodsmentioning
confidence: 99%
“…Moreover, the high sensitivity and specificity offered by this method are also higher and the drug compounds can be analyzed up to nano levels. As data are shown in table 1, these methods were widely used in quantitation of many pharmaceuticals compounds using eosin Y due to its simplicity, low cost, high sensitivity and wide concentration range [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Applications Of Spectrofluorimetry In Drug Analysis Using Eosinmentioning
confidence: 99%